Postcholecystectomy Syndrome : After Two Years And Beyond 127 Successful Laparoscopic Cholecystectomies In The Hospital Universiti Sains Malaysia - Mohamed Daud, Mohamed Ashraf (2001)

(untitled)
Cholecystectomy is considered the gold standard treatment for symptomatic gallstones disease especially with the advent of laparoscopic approach, which is known to have well documented advantages. Nevertheless, 6% to 39% of the patients continue to have either persistent symptoms or emergence of new symptoms suggestive of gallstone disease after the laparoscopic cholecystectomy. All the previous studies were looking at the postcholecystectomy symptoms or syndrome one year after the surgery. Furthermore, there is no local data regarding the postcholecystectomy syndrome as yet.